The Importance of Learning Media Utilizing (Internet-Based Arabic Lessons in Online Learning) in the Global Pandemic Era - Elly Miftahul Rohmah; Abdul Wahab Rosyidi (Shaut al Arabiyyah, 2023)
The Ministry of Education, Culture, Research, and Technology conveyed its directives to carry out online learning to prevent the spread of Corona Virus Disease (COVID-19). Through online learning, an educator can conduct face-to-face meetings with their students through applications that can be accessed by the internet network. Online learning cannot be separated from internet-based media, because online learning requires internet network access. The use of internet-based media in the era of a global pandemic is considered urgent amid the government’s policy to avoid crowds in anticipation of the spread of a global pandemic. Internet-based Arabic learning media has some urgency in online learning in the era of a global pandemic, one of the main reasons is as a connecting medium for communicating, interacting, and face-to-face with students in the midst of the spread of Covid -19.